Optimization, Characterization, and Primary Irritation Test of Serum Based on Simplex Lattice Design - Widyaningrum, Naniek; Arief, Thendi Abdul; Ningrum, Yuyun Darma Ayu (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2024)
Using ingredients in cosmetic serum formulation necessitates meticulous consideration to mitigate potential pharmaceutical and clinical issues, and guarantee their safety for application. Xanthan gum functions as a gelling agent, while sodium metabisulfite is an additional antioxidant capable of enhancing formulation viscosity. This research aimed to ascertain the optimal formula's physical characteristics, stability, and irritation potential. The optimal formula was derived through the utilization of the Simple Lattice Design. Physical characterization encompassed parameters such as pH, viscosity, organoleptic properties, adhesion, spreadability, and homogeneity. Stability testing involved a cycling test performed over 24 hours for six cycles under cold and hot temperatures. Subsequently, an analysis was conducted using the paired t-test. In-vitro primary irritation testing was carried out using rabbits and volunteers. The optimal formula was identified to consist of 0.66% xanthan gum and 0.34% sodium metabisulfite, exhibiting favorable physical quality and meeting the requisite standards. The stability testing results revealed that sig. values <0.05 indicated storage temperature's influence on viscosity enhancement while it did not influence pH with sig. values <0.08. The outcomes of the primary irritation test yielded values of 0, signifying the absence of erythema and edema in both rabbits and volunteers. In conclusion, the optimal formula derived from this study exhibits commendable characteristics, stability, and non-irritating attributes, rendering it safe for application.